Cultura de segurança do paciente na perspectiva do enfermeiro - Matiello, Raquel Duarte Correa (2015)
Introduction: In 2004, the World Health Organization defined as priority the development of research based on scientific evidence with best practices for the patient’s safety. In Brazil, in July 2013, the National Sanitary Agency (Agência Nacional de Vigilância Sanitária, ANVISA) established the Directory Resolution RDC 36, which encompasses the whole country, and which will contribute for the prioritization, by the healthcare institutions, of strengthening strategies for the risk management and the consolidation of a safety culture. To improve the safety of the patient, it is necessary to implement a safety culture as an institutional policy, although this is one of the most difficult steps for an institution to take. Initially, for that change to occur, a survey of the organizational factors that hinders the formation of this culture is crucial. Objectives: To assess the attitudes and safety culture of the patient in the Nurse’s perspective, and to identify the factors that influence in the safety of the patients. Methodology: This is a transversal study, done with Nurses who work at a tertiary assistance hospital, which is reference for oncologic treatment. The data was collected between April and May, 2015, through the application of the Safety Attitudes Questionnaire – Short Form). Results: Out of the six SAQ domains, only the Satisfaction with the Job domain presented a mean higher than 75 (78.39), being considered a positive evaluation of the work place. As for the Safety Climate, 89% of the professionals agreed that errors are treated in an appropriate way. The lower score was for the domain Perception of Management, which can indicate that the vision of the Nursing professionals for the promotion of the patient’s safety isn’t perceived by the hospital management. Conclusion: Five out of the six dimensions evaluated presented scores lower than expected, mainly in regard to the Perception of Management and the Workplace Conditions. The challenges with collaboration and communication between professionals need to be improved in order that all together might improve the safety culture and, consequently, the overall quality of the services provided to the patients.